Evaluating the Power System Operational Flexibility with Explicit Quantitive Metrics - Fei Guo; Hujun Li; Fangzhao Deng (Energies)
With carbon neutrality as a target and the increased penetration of renewable energy, the operational flexibility of power systems has begun to face challenges. In order to explicitly represent the operational flexibility of power systems, two types of flexibility indexes and corresponding models for their evaluation are established in this paper. One of the indexes is the supply–demand balance, which evaluates the adequacy of operational flexibility at the system level. The other is the availability of flexible resources, which comprehensively quantifies the flexibility of the power system from the perspectives of power generation, load, and energy storage. In the case study presented here, the proposed evaluation method is illustrated and validated based on a provincial power system in China. Next, the role of energy storage in enhancing flexibility is quantitatively analyzed using the proposed indexes. Then, the economic model reveals the nonlinear decline in the marginal benefit of investment in energy storage. Energy storage alone cannot fully meet the requirements for supply–demand balance in the power system, necessitating a comprehensive consideration of the available capacity for flexibility from the perspectives of generation, load, and energy storage. Analysis of a typical scenario shows that the provincial power system has 5000 MW of upward and downward flexibility in capacity. The numerical results highlight the critical importance of integrating flexibility across all components.